Daily activity patterns and habitat use of the lowland tapir (Tapirus terrestris) in the Atlantic Forest - Cruz, María Paula (2014)
We studied the daily activity pattern and habitat use of the lowland tapir Tapirus terrestris and their relationship with environmental and anthropic variables. We used photographic records of tapirs obtained during five camera-trap surveys conducted in three areas of the Atlantic Forest of Argentina that differ in their protection against poaching. The daily activity pattern was analyzed with circular statistics and linear regression. The effect of protection against poaching and environmental variables on habitat use of tapirs was analyzed using occupancy modeling. Tapirs were nocturnal all year round, with 89% of the records between 1800 h and 0700 h. The proportion of nocturnal records and the recording rate did not change with mean daily temperature. The daily activity pattern of tapirs was not affected by the sex of the individuals, the lunar cycle or the protection level of the area. The probability of detecting tapirs increased with the distance to the nearest access points for poachers and decreased with the abundance of bamboo in the understory and increasing trail width. The probability of use of an area by tapirs increased with increasing protection against poaching and distance to the nearest access points for poachers. These results suggest that poaching is one of the factors with significant effect on habitat use by tapirs but not on their daily activity patterns.